Structural Classification of Surigaonon, Cebuano, and Tagalog Languages: A Comparative Morpho-Lexical Analysis - CIRUELA, DENZEL MARK (International Journal of Language and Literary Studies, 2024)
This study compares the morphological affixation and lexical analysis of the Tagalog, Cebuano, and Surigaonon languages. Using a descriptive-analytical methodology, the researcher combines morphemes and scrutinizes the lexical words employed in the context to compare and contrast the three languages. Based on the study's findings, it was found that, despite having similar spelling in all three languages, some words have different meanings or registers when identifying and analyzing them. Even if each of them can cover the majority of a language's words and the method or system of affixation is nearly the same, the language still has a relationship with Surigaonon, Cebuano, and Tagalog in exposing meanings in a context, despite variations caused by geography. Regarding identification, it has been shown that the Surigaonon, Cebuano, and Tagalog languages share similarities in employing a morpheme's suffix. However, they differ in terms of the suffix used for a word. We should continue to promote and uplift the Filipino people by implementing various initiatives to foster and stimulate both our national language and the indigenous languages of the Philippines.